On American freedom : a critique of the country's core value with a reform agenda - Morris, Kenneth E.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Although freedom is America's core value, few Americans have a clear idea of what it means or - worse - enjoy much freedom in any of its conventional meanings. Drawing from republican tradition, the book critiques the contemporary American value of freedom as it appears in politics, the economy, and culture.
Keywords: Science; Science; Science, general